IMPACT OF PHYSICAL EDUCATION AND SPORTS IN PROMOTING SOCIAL VALUES AMONG YOUTH (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The purpose of this study is to investigate the impact of physical education and sports in promoting social values among youth. Physical education and sports plays a vital role in educating the youth regarding the importance of social values in their life. Reviewed literature investigated that the importance of association in educating both minds and body. Further, it also encourages the social values among youth that allow them to develop the social relations with their community. Moreover, the benefits of physical education and sports can influence both academic learning and physical activity of the youth.